Copper(i) complexes as alternatives to iridium(iii) complexes for highly efficient oxygen sensing1. Issue 57 (21st July 2015) - Medina-Rodríguez, Santiago; Orriach-Fernández, Francisco J.; Poole, Christopher; Kumar, Prashant; de la Torre-Vega, Ángel; Fernández-Sánchez, Jorge F.; Baranoff, Etienne; Fernández-Gutiérrez, Alberto
<x xml:space="preserve">Abstract</x> Cu(i) complexes outperforming Ir(iii) complexes for optical oxygen sensing are demonstrated, which creates new opportunities for low cost sensors.